Hubungan Konsumsi Natrium dan Aktivitas Fisik dengan Kejadian Hipertensi pada Masyarakat Pesisir Lingkungan Lemo-Lemo, Kabupaten Bombana - Fitri, Fitri; Ihsan, Habib; Ananda, Siti Hadrayanti (Jurnal Gizi Ilmiah, 2022)
Hypertension is a condition where blood pressure exceeds 140/90 mmHg. Hypertension can cause complications of cardiovascular diseases such as stroke, heart disease and diabetes mellitus. The number of hypertension cases in Lemo-Lemo in 2019 was 112 new cases of hypertension and in 2020 increased to 150 cases. The purpose of this study was to determine the relationship between sodium consumption and physical activity with the incidence of hypertension. Quantitative research design, cross sectional study approach. The population is all coastal communities aged 18-50 years in the Lemo-Lemo Environment, Bombana Regency as many as 180 people and a sample of 64 people obtained by Simple Random Sampling. Data were analyzed using Chi-square test and Fisher Exact. The results obtained p value of 0.014 for the relationship of sodium intake with the incidence of hypertension, p value of 0.018 for the relationship of physical activity with the incidence of hypertension, The conclusion of this study is that there is a relationship between sodium consumption and physical activity with the incidence of hypertension. The suggestion of this research is for the coastal community of the Lemo-Lemo environment, to limit the consumption of salted fish, shrimp and shell. For the government of the Lemo-Lemo Environment, to provide education related to the prevention of hypertension through limiting foods that are high in sodium and for further researchers, to analyze other factors that cause hypertension such as macronutrient intake, family history, stress factors, age and obesity factors.